Challenges to promoting eco-industry parks in Malaysia: A case study of Rawang Integrated Industrial Park - Ong, Jenny (Springer, 2021)
Malaysia is a developing country, and its economic growth has caused the increase in the generation of industrial waste in terms of its volume. The increase has its impacts towards the environment. Thus, it is imperative for the stakeholders to address the waste disposal issues in general. Currently, majority practice the end-of-pipe approach, that promotes the use of landfill disposal method. As this is not an eco-friendly solution, strategy such as recyclable material recovery is explored. This paper presents an overview of the current non-hazardous industrial solid waste management and typical challenges faced for developing eco-industrial park (EIP). In this paper, we select Rawang Integrated Industrial Park, Malaysia as our study model. A total of 29 companies in this park, which are comprised of small, medium and large industries, agreed to participate in this study. The questionnaires were distributed via email, followed by telephone calls and face-to-face interviews to increase the response rate. Results shown that 66% of the companies did not have designated personnel in solid waste management because it was not a major concern so long the waste was collected and disposed by the waste collection contractor. The common types of non-hazardous wastes generated were food wastes, waste papers, plastic wastes, glass and metals. Furthermore, none of the respondents knew where their wastes were disposed. Finally, the case study of Rawang Integrated Industrial Park suggests four typical challenges for developing eco-industrial parks in Malaysia. They were namely, low quantity of recyclable generated by industry, lack of top management commitment, absence of synergies between industries and lack of enforcement.